Fenofibrate Decreases Hepatic P-Glycoprotein in a Rat Model of Hereditary Hypertriglyceridemia - Poruba, Martin; Matuskova, Zuzana; Hüttl, Martina; Malinska, Hana; Oliyarnyk, Olena; Markova, Irena; Gurska, Sona; Kazdova, Ludmila; Vecera, Rostislav (Frontiers in Pharmacology, 2019)
P-glycoprotein (P-gp) is a membrane-bound transporter encoded by Mdr1a/Abcb1a and Mdr1b/Abcb1b genes in rodents involved in the efflux of cytotoxic chemicals and metabolites from cells. Modulation of its activity influences P-gp-mediated drug delivery and drug-drug interaction. In the current study, we tested the effects of fenofibrate on P-gp mRNA and protein content in non-obese model of metabolic syndrome. Males hereditary hypertriglyceridemic rats were fed standard laboratory diet (Controls) supplemented with micronized fenofibrate in lower (25 mg/kg b. wt./day) or in higher (100 mg/kg b. wt./day) dose for four weeks. Liver was used for the subsequent mRNA and protein content analysis. Fenofibrate in lower dose decreased hepatic Mdr1a by 75 % and Mdr1b by 85 % while fenofibrate in higher dose decreased Mdr1a by 90 % and Mdr1b by 92 %. P-gp protein content in the liver was decreased by 74 % in rat treated with fenofibrate at lower dose and by 88 % in rats using fenofibrate at higher dose. These findings demonstrate for the first time that fenofibrate decreases both mRNA and protein amount of P-gp and suggest that fenofibrate could affect bioavailability and interaction of drugs used to treat dyslipidemia-induced metabolic disorders.